Ectoparasites of pigeons Columba livia traded in a market of the district of San Martín de Porres, Lima, Peru - Naupay I., Asucena (2015)
The aim of this study was to determine the prevalence, average intensity and mean abundance of ectoparasites in domestic pigeons (Columba livia). A total of 29 specimens were analyzed (17 males and 12 females). External surface of head, neck, chest, back and wings were examined, determining that 93.1% (14.9 ± 15.8 of total mean abundance) of pigeons were infected with one or more ectoparasites. All males and 83.3% of females were parasitized. Seven species of ectoparasites were identified, where five correspond to Order Mallophaga (Columbicola columbae [82.8%], Menopon gallinae [48.3%] Goniodes gigas [31%], Menacanthus stramineus [17.2%] and Lipeurus caponis [6.9%]), one to Order Diptera (Pseudolynchia canariensis [10.3%]), and one to Order Siphonapetra (Echidnophaga gallinacea [3.4%]). The largest number of mallophagans was found on the feathers of the wings and chest. Among associations, the monoparasitism was present in 28%, biparasitism in 28%, triparasitism in 34% and tetraparasitism in 3% of the pigeons. C. columbae was the most prevalent ectoparasite (82.8%). Besides, Menacanthus stramineus and Lipeurus caponis are reported for the first time as ectoparasites of Columba livia in Peru.